The Effect of Leadership, Work Stress, and Work Conflict on Employee Turnover Intention - Refli Renaldi; Nur Ainun; Sandhi Fialy Harahap (Yayasan Multidimensi Kreatif, 2024)
This study examined how leadership (X1), work stress (X2), and work conflict (X3) affect turnover intention (Y) among Bengkel Auto Star Plus Medan employees. This study included 40 Bengkel Auto Star Plus Medan employees. This study sampled 40 persons. A 2021 study was undertaken. This study employed SPSS 24.0 to process quantitative data from a multiple linear regression model. Work stress and conflict had a favourable and statistically significant effect on Bengkel Auto Star Plus Medan employees' turnover intention, but leadership had no effect. Leadership, work stress, and work conflict affected Bengkel Auto Star Plus Medan employees' turnover intentions. With the greatest t-count value of 4.596, work stress influenced turnover intention the most. 88. Leadership, stress, and workplace conflict explained 5% and predicted 11.5% of desire to leave. Leadership, job stress, and conflict affect employees' inclinations to leave.